2022
DOI: 10.3390/cells11111748
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Marks, DNA Damage Markers, or Both? The Impact of Desiccation and Accelerated Aging on Nucleobase Modifications in Plant Genomic DNA

Abstract: Modifications of DNA nucleobases are present in all forms of life. The purpose of these modifications in eukaryotic cells, however, is not always clear. Although the role of 5-methylcytosine (m5C) in epigenetic regulation and the maintenance of stability in plant genomes is becoming better understood, knowledge pertaining to the origin and function of oxidized nucleobases is still scarce. The formation of 5-hydroxymetylcytosine (hm5C) in plant genomes is especially debatable. DNA modifications, functioning as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Such results indicate, that irrespective to anticipated mechanisms (enzymatic vs. driven by oxidative agents possibly released by the excited photosynthetic system) ongoing in hydrated or dried cytoplasm [13,16], a similar change in DNA methylation occurs during seed deterioration. This is in concordance with the latest research on recalcitrant Acer pseudoplatanus L. embryonic axes showing 5mC decline in tissues subjected to severe desiccation or accelerated aging [53]. Therefore, in the next step, all results for each seed lot were pulled together (Figure 5a,b).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Such results indicate, that irrespective to anticipated mechanisms (enzymatic vs. driven by oxidative agents possibly released by the excited photosynthetic system) ongoing in hydrated or dried cytoplasm [13,16], a similar change in DNA methylation occurs during seed deterioration. This is in concordance with the latest research on recalcitrant Acer pseudoplatanus L. embryonic axes showing 5mC decline in tissues subjected to severe desiccation or accelerated aging [53]. Therefore, in the next step, all results for each seed lot were pulled together (Figure 5a,b).…”
Section: Discussionsupporting
confidence: 86%
“…This premise is supported by the fact that heterochromatic chromocentromers are smaller just after germination than they are at three weeks after germination and during germination [51,52]. Notably, the opposite trend in changes in the level of global DNA methylation has been observed in recalcitrant seeds of exceptional desiccation-sensitive species (EF2) Acer pseudoplatanus L. In those seeds, desiccation induced a decrease in the level of 5mC, which was significantly related to a decrease in their viability [37,53]. Therefore, our data show for the first time that the desiccation-induced epigenetic response of intermediate seeds produced by the exceptional plant species (EP 3) P. nigra is similar to the response observed in orthodox seeds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, when DNA methylation level was analyzed, the sudden decline was noticed in embryonic axes desiccated to this MC, and it remained constant in further desiccation steps. Previously, we showed that viability decline of orthodox and recalcitrant seeds subjected to desiccation [ 29 , 55 ] is highly correlated with decline of DNA methylation level in embryonic axes isolated from seeds of these categories. Hypomethylation-related viability decline in A. thaliana tissues was also reported [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, also in our experiment the level of MC was higher in embryonic axes at the time of collection and during desiccation ( Table S1 ), and DNA methylation changes that correlated with seed deterioration were observed only for embryonic axes. Moreover, we perceive the link between imbalance in cellular redox environment of beech seeds and ROS-related effect on DNA methylation [ 29 , 55 , 58 ]. It was previously shown that embryonic axes of beech are exposed to a greater degree to detrimental chemical reactions leading to oxidative stress and ROS overproduction and consequently to the multiple and diverse damages to metabolism and cellular structures [ 16 , 41 ].…”
Section: Discussionmentioning
confidence: 99%